Pathological investigations on the diseases of rainbow trout (oncorhynchus mykiss w., 1792) in aydın and muğla regions - S. Serap Birincioğlu; Nursal Metin; Hamdi Avcı; Ahmet Aydoğan; Fatma Sayın (Eurasian Journal of Veterinary Sciences)
Aim: The aims were to determine pathological findings in diseased fish in rainbow trout farms and to emphasize the importance of there findings in the diagnosis of fish diseases. Material and Method: A total of 150 diseased fish obtained from the fish farms in Aydin and Muğla regions were examined. Following the macroscopic examinations, tissue samples were processed routinely and parafin embedded. The tissiues were sectioned at 5 μm, stained with hematoxylin and eosin and then examined by light microscopy. Results: Macroscopically, erosive and ulcerative lesions on the surface of the skin, exophthalmos and hemorrhages in the eyes, hyperemia and hemorrhage in the gills and hemorrhage and discoloration on the liver were observed. Microscopically, edema, hyperemia, telangiectasia, hemorrhage, hyperplasia parasites (Trichodina sp., Ichthyophthirius multifiliis) were determined in the gills. In the heart, epicarditis in 38 fish and myocarditis in 13 fish was seen. Lesions of the liver were degeneration, fatty changes and lymphoid cells infiltrations. The kidney showed hemorrhage, hyaline droplets in the epithelium of the proximal tubuli and increases in melanomacrophage centers. Focal necrosis in the spleen was seen in only 4 fishes. Conclusion: The results revealed that multidisciplinary studies including histopathologic examinations were very important for accurate diagnosis and effective treatment in the diagnosis of fish diseases.